Predictors of COVID-19 Vaccine Acceptance, Intention, and Hesitancy: A Scoping Review - Ashish Joshi; Mahima Kaur; Ritika Kaur; Ashoo Grover; Denis Nash; Ayman El-Mohandes (Frontiers Media S.A., 2021)
COVID-19 vaccine is regarded as the most promising means of limiting the spread of or eliminating the pandemic. The success of this strategy will rely on the rate of vaccine acceptance globally. The study aims to examine the factors that influence COVID-19 vaccine acceptance, intention, and hesitancy. PubMed was searched comprehensively for articles using the keyword "COVID-19 vaccine surveys." Of the 192 records, 22 studies were eligible for the review. Eighty-two percent of these studies were conducted among the general population. Gender, age, education, and occupation were some of the socio-demographic variables associated with vaccine acceptance. Variables such as trust in authorities, risk perception of COVID-19 infection, vaccine efficacy, current or previous influenza vaccination, and vaccine safety affected vaccine acceptance. Globally, in March 2020, the average vaccine acceptance observed was 86% which dropped to 54% in July 2020 which later increased to 72% in September 2020. Globally, the average rate of vaccine hesitancy in April 2020 was 21%, which increased to 36% in July 2020 and later declined to 16% in October 2020. Large variability in vaccine acceptance and high vaccine hesitancy can influence the efforts to eliminate the COVID-19. Addressing the barriers and facilitators of vaccines will be crucial in implementing effective and tailored interventions to attain maximum vaccine coverage.